EDUKASI IBU BALITA UPAYA PENCEGAHAN STUNTING - Ridni Husnah; Ayu Mutia Lestari; Fitriani Fitriani (COVIT (Community Service of Health), 2022)
The government has launched a National Action Plan program for handling stunting at the national level, especially villages. The age of 0–2 years or the age of under three years (toddler) is a golden age for the growth and development of children, because at that time there is a very rapid growth. The period of the first 1000 days is often called the window of opportunities or this golden period is based on the fact that in the fetal period until the child of two years of age there is a very rapid growth and development process that does not occur in other age groups. From the results of interviews with several mothers who have toddlers in the Malacca Legends Housing, it is known that they have not been exposed to much about stunting. So some of them think that their children / toddlers shorter than their age are genetic factors so they do not need further treatment. The method of implementation in the community service program through providing counseling on stunting to mothers in the malacca legend housing through 3 (three) stages, namely the implementation strategy meeting, location survey, then preparation of facilities and infrastructure. The population in this study were mothers in The Malacca Legends Housing Block H, while the Samples were mothers in the Malacca Legends Housing Block H who had babies and toddlers. The stage of implementing mentoring activities for mothers is divided into 3, namely, anthropometric measurements are carried out to find out data on weight and height and age to find out the nutritional status of toddlers, then continued with counseling about stunting, ways of prevention and community participation in handling stunting. After counseling, it is continued with a post-test to measure mothers' knowledge after community service activities are carried out. Parents and the community around Housing Legends Malacca Blok H Batam are mostly high school educated. Parents' knowledge about stunting prevention programs based on pre-test results, most mothers of toddlers do not know about stunting prevention. Meanwhile, based on the post test results, almost all mothers of toddlers understand about the implementation of the stunting program. Keywords : Toddler Mother, Stunting